Intersectional criminology: interrogating identity and power in criminological research and theory - Potter, Hillary (Critical criminology, 2013)
Intersectional criminology is a theoretical approach that necessitates a critical reflection on the impact of interconnected identities and statuses of individuals and groups in relation to their experiences with crime, the social control of crime, and any crime-related issues. This approach is grounded in intersectionality, a concept developed from the tenets of women of color feminist theory and activism. To demonstrate how intersectionality is useful in criminology, this article reviews a sampling of feminist and critical research conducted on Black girls’ and women’s experiences with crime, victimization, and criminal legal system processes. This research demonstrates the interlaced social impacts of race, gender, femininity/masculinity ideals, sexuality, and socioeconomic class. This article also provides a basis for widely deploying an intersectional approach throughout the field of criminology across all social identities and statuses.